Loss of a single tree species will lead to an overall decline in plant diversity: Effect of Dracaena cinnabari Balf. f. on the vegetation of Socotra Island. (April 2016) - Rejžek, Martin; Svátek, Martin; Šebesta, Jan; Adolt, Radim; Maděra, Petr; Matula, Radim
Abstract: Dracaena cinnabari, the dominant endemic tree of Socotra Island (Yemen), is in serious decline. The effect this will have on the island's plant diversity remains unknown. We aimed to identify plants associated with Dracaena understorey and assess the importance of Dracaena for maintaining plant diversity. A total of 272 relevés were sampled in Dracaena understorey and in open sites to record the number of individuals of vascular plants. Species richness and composition were compared between understorey and open sites, and species associated with each of these habitats were identified. Additionally, the effect of canopy closure on species richness and abundance was analysed. We also recorded woody species composition of Dracaena stands and investigated spatial relations between Dracaena and other mature woody plants. Understorey plant species composition differed from open site composition. The former habitat showed higher β-diversity and species richness. Among recorded plants, 15 species were classified as understorey specialists, 6 as open-site specialists, and 23 as generalists. Rare species, especially endemics, were more common in the understorey. Canopy closure had differential effect on species abundances among the species classes. Species richness and total abundance were found to be highest in the understorey, particularly in the case of low-to-intermediate canopy closure where understorey and open-site specialists may co-occur. For mature woody plant species, Dracaena was spatially independent from other woody species at most distances. Our results suggest that the decline of Dracaena may negatively affect plant diversity, reduce abundance of rare endemic plants and lead to homogenization of vegetation. As no other tree species exists in the study area which could replace the Dracaena, our findings underline the importance of conservation efforts to preserve Dracaena stands on Socotra. Graphical abstract: Highlights: Dracaena understorey plant species composition differs from open site composition. Species richness and total abundance are higher in the understorey. Ongoing decline of Dracaena may negatively affect associated endemic-rich vegetation. Results underline the importance of conservation efforts to preserve Dracaena stands.